The earliest thymic progenitors for T cells possess myeloid lineage potential - Bell, J. Jeremiah; Bhandoola, Avinash (Nature, 2008)
Redrawing the blood lines In the current dominant model of haematopoiesis, T cells are thought to arise from lymphoid-restricted common lymphoid progenitors, and myeloid cells (including granulocytes and macrophages, found in bone marrow and spinal cord) from progenitors committed to the myeloid lineage. Two papers in this issue report evidence that contradicts this. Rather, they find a single type of progenitor in adult thymus with both T and myeloid potential. T cells are produced by an early population in the thymus that has lost the ability to produce B cells, but still produces macrophages and cells with T, NK (natural killer) and dendritic cell potential. These results support a model for haematopoiesis where the progenitor cell at the branch point of T and B cell lineages retains macrophage potential. One of two papers that show there is a single type of progenitor within the adult thymus that possesses both T and myeloid potential. It is shown that T cells are produced by an early population in the thymus that has lost the ability to produce B cells, but can still produce macrophages as well as cells with T, NK and dendritic cell potential. These papers therefore argue against the classical dichotomy model in which T cells are derived from common lymphoid progenitors, and support a model for adult hematopoeisis where the progenitor cell at the branch point of the T and B cell lineages retains macrophage potential. There exists controversy over the nature of haematopoietic progenitors of T cells. Most T cells develop in the thymus, but the lineage potential of thymus-colonizing progenitors is unknown. One approach to resolving this question is to determine the lineage potentials of the earliest thymic progenitors (ETPs). Previous work has shown that ETPs possess T and natural killer lymphoid potentials, and rare subsets of ETPs also possess B lymphoid potential 1 , suggesting an origin from lymphoid-restricted progenitor cells. However, whether ETPs also possess myeloid potential is unknown. Here we show that nearly all ETPs in adult mice possess both T and myeloid potential in clonal assays. The existence of progenitors possessing T and myeloid potential within the thymus is incompatible with the current dominant model of haematopoiesis, in which T cells are proposed to arise from lymphoid- 2 . Our results indicate that alternative models for lineage commitment during haematopoiesis must be considered.